L'injustice épistémique : questions de vérité et méthode - Coline Sénac (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2022)
This article proposes the comparison of two methods of analysis, semiotics, and hermeneutics, to address contemporary issues in ethical and political philosophy, through the study of the phenomenon of epistemic injustice. Conceptualized by Fricker (2007), epistemic injustice is synonymous with the denial of the value of knowledge that an individual possesses because of prejudices about the social group to which he or she belongs or is affiliated. When epistemic injustice is studied in the empirical world, it poses some crucial issues in terms of interpreting the meaning that the individual gives to the experience of injustice that he or she experiences.